Small-Molecule Activity-Based Probe for Monitoring Ubiquitin C-Terminal Hydrolase L1 (UCHL1) Activity in Live Cells and Zebrafish Embryos - Kooij, Raymond (J Am Chem Soc, 2020)
[Image: see text] Many reagents have emerged to study the function of specific enzymes in vitro. On the other hand, target specific reagents are scarce or need improvement, allowing investigations of the function of individual enzymes in their native cellular context. Here we report the development of a target-selective fluorescent small-molecule activity-based DUB probe that is active in live cells and an in vivo animal model. The probe labels active ubiquitin carboxy-terminal hydrolase L1 (UCHL1), also known as neuron-specific protein PGP9.5 (PGP9.5) and Parkinson disease 5 (PARK5), a DUB active in neurons that constitutes 1 to 2% of the total brain protein. UCHL1 variants have been linked with neurodegenerative disorders Parkinson’s and Alzheimer’s diseases. In addition, high levels of UCHL1 also correlate often with cancer and especially metastasis. The function of UCHL1 activity or its role in cancer and neurodegenerative disease is poorly understood and few UCHL1-specific activity tools exist. We show that the reagents reported here are specific to UCHL1 over all other DUBs detectable by competitive activity-based protein profiling and by mass spectrometry. Our cell-penetrable probe, which contains a cyanimide reactive moiety, binds to the active-site cysteine residue of UCHL1 in an activity-dependent manner. Its use is demonstrated by the fluorescent labeling of active UCHL1 both in vitro and in live cells. We furthermore show that this probe can selectively and spatiotemporally report UCHL1 activity during the development of zebrafish embryos. Our results indicate that our probe has potential applications as a diagnostic tool for diseases with perturbed UCHL1 activity.